Pengaruh Pengelolaan Aset Desa, Alokasi Dana Desa, Badan Usaha Milik Desa Terhadap Pendapatan Asli Desa(Studi Kasus Desa Cangkol Kecamatan Mojolaban Kabupaten Sukoharjo) - Leny Putri Melati; Setyaningsih Sri Utami (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study was conducted in Cangkol Village, Mojolaban Subdistrict, Sukoharjo Regency, with the main objective of analysing the significance of the influence of various sources of funds and village enterprises on Village Original Income (PADes). This study used a quantitative approach relying on secondary data. The analysis methods applied included descriptive analysis, classical assumption testing, multiple linear regression analysis, T-test, F-test, and coefficient of determination (R2). The results showed that Village Asset Management (PADes) had a significant effect on village revenue, proving the first hypothesis. However, Village Fund Allocation (ADD) and Village-Owned Enterprises (BUMDesa) partially did not show a significant effect, so the second and third hypotheses were not proven. Nevertheless, collectively, the three variables of Village Asset Management, Village Fund Allocation, and Village-Owned Enterprises together had a significant effect on Cangkol Village Expenditure, which strengthened the fourth hypothesis.